Follow The Line: Development and Design to Upgrade Materials for Teaching Writing Skills for Students - Faisol, Faisol; Saputra, Riski Janu; Sari, Devi Rafika; Bahruddin, Uril (Institut Agama Islam Negeri Curup, 2024)
This research aimed to develop teaching materials for writing skills with the Follow the Line Method as a solution to the difficulties in writing Arabic sentences for students at the elementary level. There are difficulties in writing Arabic sentences among non-Arabic students, especially students in the beginning stages. These difficulties cause many mistakes in writing Arabic letters and sentences even though most of them do not know how to write Arabic sentences. The method used in this research was the research and development method using the ADDIE model. The techniques employed for data collection included observation, interviews, questionnaires, and tests. The population in this research consisted of fifth grade students, with a sample size of 33 students. The results of this study were as follows: 1) Development of teaching materials for writing skills with the Follow the Line method using the ADDIE model, namely: analysis, design, development, implementation, and evaluation. 2) The use of the developed teaching materials proved effective in its application. Judging from the results obtained from Asymp. Sig. (2-tailed), the value (0.000) was smaller than 0 = (0.05), indicating a difference between the average results of students in the pre-test and post-test. The theoretical result of this study is that learning to write Arabic for beginners with the Follow the Line Method makes it easier for students to write Arabic letters and words.